The Role of Trust: Teacher Capacity During School Leadership Transition - Hong, Ji; Cross Francis, Dionne; Wang, Qian; Lewis, Laura; Parsons, Alexandra; Neill, Crystal; Meek, Diana (Frontiers in Education, 2020)
The purpose of this research is to examine teachers’ capacities and the role trust plays in the professional lives of teachers during the transition to a new team of three administrators in an elementary school located in a low-income urban community in the United States. Twenty-seven teachers’ surveys and interviews showed that the transition caused some level of instability and uncertainty; however, teachers had a positive sense of efficacy, social capital, resilience, and emotions. The four themes that emerged from the interviews—common goals and vision for students, beliefs in colleagues’ competence, emotional safety and comfort, and being vulnerable with colleagues—appear to function as conditions to build trust among colleagues. The trusting relationships seem to help teachers withstand the challenging transition by providing a safe space where teachers can learn and grow. Implications for school administrators and district offices were discussed.